Meneroka faktor-faktor yang menyumbang kepada hakisan integriti dalam kalangan kakitangan pendidikan di Malaysia: satu kajian kes di negeri Perlis - Hamdah, Nor Halmey (2024)
This study explores the factors contributing to the erosion of integrity among education personnel in Perlis, Malaysia, through the lens of institutional theory. The main objective is to investigate the institutional pressures, norms, and practices that shape the ethical behavior of education personnel as well as offer suggestions to promote and maintain integrity within the education system. The study employs a qualitative research design, involving document analysis, in-depth interviews, and focus group discussions to collect data from education personnel in Perlis. The key findings reveal the pervasive influence of institutional pressures, the importance of fostering a shared understanding of integrity, the impact of institutional practices on ethical behavior, the crucial role of leadership and role modeling, as well as the value of open dialogue and recognition of ethical conduct. The study also highlights the interaction between individual agency and institutional forces in shaping ethical behavior, calling for a balanced and holistic approach to promote integrity. The findings have significant implications for policies, practices, and future research, emphasizing the need for a comprehensive, collaborative, and evidence-based approach in promoting ethical excellence in education. The study contributes to a more nuanced understanding of the challenges and opportunities in cultivating a culture of integrity within the Malaysian education sector and supports efforts to build a more fair, transparent, and accountable education system.